Anticipatory grief and impaired problem solving among surrogate decision makers of critically ill patients: A cross-sectional study. (December 2018) - Glick, Danielle R.; Motta, Melissa; Wiegand, Debra L.; Range, Patrick; Reed, Robert M.; Verceles, Avelino C.; Shah, Nirav G.; Netzer, Giora
Abstract: Objectives: Anticipatory grief, the experience of grief before the death of a mourned individual, is common among people with seriously ill loved ones and associated with impaired social problem solving. We sought to evaluate anticipatory grief in the Intensive Care Unit setting. Research methodology/design: Cross-sectional study of surrogate decision-makers of patients admitted to an intensive care unit, incorporating survey methodology. Setting: Intensive care units at a tertiary care centre. Main outcome measures: Surrogates completed a 78-question, self-administered questionnaire consisting of demographic and clinical data, as well as three validated instruments: Anticipatory Grief Scale (AGS), Hospital Anxiety and Depression Scale (HADS), and Social Problem Solving Inventory Revised Short Form (SPSI-R:S). Main results: Surveys were completed by 50 surrogate decision-makers, among whom anticipatory grief was elevated and associated with anxiety and depression. Anticipatory grief was also significantly associated with worsened overall problem solving (Spearman's Rho −0.32, p value 0.02). Surrogates with loved ones who were older or admitted to a trauma unit experienced anticipatory grief at lower levels. Prior admission and Charlson Comorbidity Index scores were not associated with anticipatory grief. Conclusion: Levels of anticipatory grief in the intensive care unit are high and associated with concurrent anxiety and depression. Association of anticipatory grief with worsened social problem solving may worsen decision making ability in surrogates.